First-order convergence of Milstein schemes for McKean–Vlasov equations and interacting particle systems. (6th January 2021) - Bao, Jianhai; Reisinger, Christoph; Ren, Panpan; Stockinger, Wolfgang
Abstract : In this paper, we derive fully implementable first-order time-stepping schemes for McKean–Vlasov stochastic differential equations, allowing for a drift term with super-linear growth in the state component. We propose Milstein schemes for a time-discretized interacting particle system associated with the McKean–Vlasov equation and prove strong convergence of order 1 and moment stability, taming the drift if only a one-sided Lipschitz condition holds. To derive our main results on strong convergence rates, we make use of calculus on the space of probability measures with finite second-order moments. In addition, numerical examples are presented which support our theoretical findings.